Emotional intelligence in male and female sport climbers - Milena Marczak; Michał Ginszt (Kazimierz Wielki University, 2017)
Background: Emotions are a fundamental aspect of the sport activity manifesting itself in mental and physiological processes. In sport training, they act as motivational, informative and communicative factors. The ability to recognize emotional states, understand them, and express themselves in sport activity is an aspect of emotional intelligence that contributes to success in sport performance. Aim: The aim of presented study is to compare the emotional intelligence traits in male and female sport climbers. Material and methods: We examined 60 sport climbers (30 men, 30 women) aged 23±1 years. The average time of climbing training was 6 years. The study used the Popular Emotional Intelligence Questionnaire (PKIE). PKIE consists of 94 items of self-assessment. The questionnaire allows to calculate results on four-factor scale and the overall score. Results: The results showed there were significant differences between the two groups on the scale of emotions control, understanding and realizing own's emotions and in general indicator of emotional intelligence. In the indicated scales, men achieved higher average results. There were no significant differences in accepting, expressing and using emotions on both action and empathy scales. Conclusions: Male sport climbers used the recognition and understanding of emotional states to solve problems for success in climbing and characterize their higher level of overall emotional intelligence in a better way. Sport climbers of both sexes had average levels of acceptance of emotion and empathy. This means that climbers of both sexes were characterized by low levels of other emotional experiences and the use of emotional experiences in prospective activities.